OPTIMIZATION OF STRUCTURAL REFOLDING OF SPIKE 1 RECOMBINANT PROTEIN FROMS SARS-COV-2 WITH CHEMICAL ADDITIVES - Michelle Widyadi, Alberta
Severe acute respiratory síndrome coronavirus 2 (SARS-CoV-2) is a virus that caused coronavirus disease 2019 (COVID-19). This virus has four structural proteins, one of them is spike protein which plays a crucial role in receptor recognition and virus membrane fusion in cells. The spike protein consists of two subunits, S1 and S2, where on the S1 subunit there is a domain called Receptor Binding Domain (RBD) that can interact with receptor human Angiotensin Converting Enzyme-2 (ACE-2) in the S1 subunit. S1 Protein from SARS-CoV- 2 which is expressed in Escherichia coli forms an inclusion body that indicates the protein has lost its native structure. This study aims to determine the optimum buffer condition to refold S1 recombinant protein. First, competent cell E. coli BL21 CodonPlus (DE3) RIPL is transformed with recombinant plasmid pET-16b that carries genes that encoded the S1 protein. Protein that is expressed as an inclusion body is solubilized using 7,3 M urea. Soluble protein was then purified by Ni-NTA affinity chromatography and refolded using slow dilution method. The next process is to characterize the folded protein with sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) and Circular Dichroism (CD) spectroscopy. Cells that contain plasmid pET-16b-S1 were grown in Luria Bertani media with ampicillin and produce S1 recombinant protein after induced by 0,3 mM isopropyl-?- D-thiogalactoside (IPTG). A band in the size ~75 kDa is observed in the SDS-PAGE electrophoregram lysis cell crude extract. This band corresponds with the size of the S1 recombinant protein from the amino acid composition. Cell lysis result showed that S1 recombinant protein is expressed as an inclusion body. The purification process of solubilized S1 protein inclusion bodies in unfolding buffer containing 7.3 M urea was successfully carried out where a single band with a size of 75 kDa was obtained. The purified protein was then refolded using three different additives, N-lauroyl sarcosine, arginine, and sucrose. Highest percentage recovery, which is 95,4%, was obtained using buffer that contained sucrose. Sucrose can stabilize the refolded protein by creating an ideal environment for protein where water molecules can surround protein. Secondary structure percentage from CD spectrum measurement shows similarities with spike protein structure with PDB code 6VXX. These similarities confirmed that the refolding process has returned the protein to the native structure, with sucrose as the optimum additive.